The Analysis of Figurative Language in Poem “Alone” by Maya Angelou - Mega Tria Ananda; Alya Yumna Adristi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This Journal was written to find figurative language in the poem “Alone” by Maya Angelou with the aim that readers can more easily understand the meaning of this poem through the figurative language we found. The focus of this study is figurative language which involves; Metaphor, Simile, Symbolism, Alliteration, and Personification. This research used qualitative data collection method where the researcher increase the representative data. The result of this study showed there were 11 figurative language in poem Maya Angelou “Alone”, There were ; 2 Metaphor, 2 Personification, 1 simile, 4 alliteration, and 2 symbolism. The researchers concluded that they had found 11 figurative language in one of Maya Angelou's poetry works entitled